Lifestyle Behaviors and Cognitive Outcomes in Physiotherapy Students: Cross-Sectional Study - Anggraeni, Risa Kusuma; Sirada, Andy (jitek, 2025)
Background: The pervasive use of digital devices, coupled with irregular sleep and low physical activity, poses potential risks to cognitive outcomes in university students. Physiotherapy students, whose education demands both mental and physical engagement, may be particularly vulnerable. Objective: This study aimed to investigate the integrated effects of smartphone use, physical activity, and sleep quality on cognitive outcomes among undergraduate physiotherapy students. Methods: A cross-sectional design was applied involving 100 first- and second-year physiotherapy students at Universitas Pembangunan Nasional Veteran Jakarta. Data were collected through validated self-administered questionnaires, including the Cognitive Failures Questionnaire (CFQ), International Physical Activity Questionnaire – Short Form (IPAQ-SF), and a Likert-based assessment of smartphonerelated lifestyle impact. Descriptive statistics, Pearson correlation, and multiple regression analyses were performed using SPSS version 26.0. Results: The findings showed a significant relationship between excessive digital device use and increased cognitive failures. Poor sleep quality was also associated with greater cognitive lapses, while higher physical activity levels correlated positively with better cognitive performance. Regression analysis indicated that the three lifestyle variables jointly explained a substantial proportion of the variance in cognitive outcomes. Conclusion: Digital habits, sleep patterns, and physical activity levels interactively influence cognitive outcomes in physiotherapy students. Interventions promoting digital hygiene, adequate sleep, and physical activity may enhance cognitive resilience and academic performance in this population.